Screening of tissues and serum by culture, peR and ELISA for the detection of Mycobacterium avium subspecies paratuberculosis from cases of clinical ovine Johne’s disease in farmer’s flocks - SINGH, P K; SINGH, S V; SINGH, A V; SOHAL, J S (The Indian Journal of Animal Sciences, 2011)
The study was carried-out to esthnate the presence of Mycobacteriurn avium subspecies paratuberculosis in cases of clinical ovine Johne s disease (OlD) in faImer’s flocks of Rajasthan, using multiple diagnostic tests (culture, peR and ELISA). Seventy eight tissues (mesenteric lymph nodes and intestine near ilea-caecal region) and 39 serum samples were collected from 39 slaughtered sheep. Tissues were decontaminated and inoculated on Herrold’s egg yolk medium for cultivation of MAP bacilli and remaining sediment was processed for recovery of DNA and 18900 PCR. Indigenous ELISA, originally developed for goats was adopted for screening of sheep. MAP was recovered from 64.1% sheep (41.0 intestine and 38.5% MLN tissues). In IS900 peR, 48.7% sheep were positive (33.3% each in intestine and MLN). Culture and peR together detected 69.2% sheep positive (64.1 %. in culture and 48.7% in peR). Using ELISA kit, 46.1%(strong positive in S:P ratio) sheep were sera-positive for MAP infection. Of these 88.8 and 61.1% were positive in culture and peR, respectively. Of these 88.8 and 61.1% were positive in culture and peR, respectively. Comparison of 2 tests (direct peR and ELISA) with tissues culture by ’Kappa statistics’ revealed ’substantial agreement’ using nlultiple tests (culture, peR and ELISA). Study revealed high presence of MAP (74.3% sheep positive), in clinical cases of ovine lohne’s disease in fanners flocks of Rajasthan. Â